EFEKTIVITAS METODE PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY UNTUK MENINGKATKAN PEMAHAMAN MEMBACA PADA MATA KULIAH DOKKAI 3 - Nuke Lady Adistira; Arza Aibonitika; Nana Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is a weak experiment study with the design of one group one pretest-posttest which is characterized by the absence of a comparison class. The purpose of this research was to determine the effectiveness of Cooperative learning method type Two Stay Two Stray in improving reading comprehension in study Dokkai 3. There are several obstacles that make it difficult for students to read and understand Japanese reading texts (dokkai). These difficulties occur because of the limited vocabulary that is owned, the sentence patterns that are not understood and many of written or kanji used so that learners find it difficult and bored in following the study Dokkai and learning objectives are not achieved. To overcome some of the difficulties learners, a learning method is given, namely Cooperative Learning Method type Two Stay Two Stray. Based on the results of research that has been done, there is an increase in scores obtained by students, especially in understanding the contents of the text reading (dokkai). This is supported by the results of statistical tests on the pretest and posttest data that have been done.Key Word : Dokkai, Two Stray Two Stay, Student